2014
DOI: 10.1103/physrevb.90.094501
|View full text |Cite
|
Sign up to set email alerts
|

Kelvin waves and the decay of quantum superfluid turbulence

Abstract: We present a comprehensive statistical study of free decay of the quantized vortex tangle in superfluid 4 He at low and ultra-low temperatures, 0 T 1.1 K. Using high resolution vortex filament simulations with full Biot-Savart vortex dynamics, we show that for ultra-low temperatures T 0.5 K, when the mutual friction parameters α ≃ α ′ < 10 −5 , the vortex reconnections excite Kelvin waves with wave lengths λ of the order of the inter-vortex distance ℓ. These excitations cascade down to the resolution scale ∆ξ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 58 publications
5
27
1
Order By: Relevance
“…with t V = γ ζκL0 (where L 0 = L(0)). Such decay with a universal prefactor, corresponding to ζ ≈ 0.10, was observed in QT generated after a brief injection of ions in cells of different sizes [11,13] and also in numerical simulations of Vinen QT [25,26].…”
mentioning
confidence: 74%
“…with t V = γ ζκL0 (where L 0 = L(0)). Such decay with a universal prefactor, corresponding to ζ ≈ 0.10, was observed in QT generated after a brief injection of ions in cells of different sizes [11,13] and also in numerical simulations of Vinen QT [25,26].…”
mentioning
confidence: 74%
“…In superfluids it has been suggested that cascades of Kelvin waves can transfer energy from the scale of the intervortex spacing down to smaller scales, as small as the vortex core [106,55,144]. Therefore, Kelvin modes become an important mechanism in the decay of turbulence [94] as energy is directed to the smaller scales of the system, where it is eventually dissipated.…”
Section: Kelvin Wavesmentioning
confidence: 99%
“…21 Our method of making a reconnection follows that of other authors. 17,[22][23][24][25] Traditionally one reconnects two vortices as soon as any two points approach closer than some given distance. This critical distance is typically taken to be of the order of the resolution.…”
Section: Model and Equationsmentioning
confidence: 99%